2017
DOI: 10.18632/oncotarget.23289
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 sustains pro-tumorigenic signals in colon cancer tissue

Abstract: Interleukin-34 (IL-34), a cytokine produced by a wide range of cells, binds to the macrophage colony-stimulating factor receptor (M-CSFR-1) and receptor-type protein-tyrosine phosphatase zeta (PTP-z) and controls myeloid cell differentiation, proliferation and survival. various types of cancers over-express IL-34 but the role of the cytokine in colorectal cancer (CRC) remains unknown. We here investigated the expression and functional role of IL-34 in CRC. A more pronounced expression of IL-34 was seen in CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 42 publications
4
82
0
Order By: Relevance
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
See 4 more Smart Citations
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
“…Furthermore, IL‐34 induces STAT3 activation and miRNA‐21 increment in synovial fibroblast, resulting in increased resistance of fibroblast to apoptosis in RA . In an autocrine manner, IL‐34 provides a critical survival signal to CSF‐1R‐expressing cancer cells by enhancing activation of ERK1/2 and AKT signaling pathways and thus contributes to chemoresistance such as in lung and colon cancer cells in addition to malignant pleural mesothelioma cells . On the other hand, IL‐34 can inhibit the proliferation in other cells such as glioblastoma cells via a PTP‐ζ‐dependent mechanism …”
Section: Biological Functions Of Il‐34mentioning
confidence: 99%
See 3 more Smart Citations